Acute and prolonged hip kinematic changes after three different Kinesio Taping® interventions: A randomized placebo-controlled trial - Kiseljak Dalibor (Biomedical Human Kinetics)
Study aim: This study aimed to compare the acute and prolonged effects of three different Kinesio Taping (KT) techniques (underactive/overactive muscle correction [UMC]/[OMC] and functional correction [FC]) on hip ROM in the sagittal plane and compare them to those of the placebo Kinesio Taping (PKT) application.